High-resilience soft foamed polyethylene material and preparation method thereof
Through modified filler and chemical foaming processes, high-resilience soft foamed polyethylene materials were prepared, which solved the problem of insufficient antibacterial and mechanical properties of existing polyethylene materials, and achieved efficient antibacterial and sports equipment such as yoga mats and Resilience and maintain the lightweight and low-cost characteristics of polyethylene materials.
Patent Information
- Application Number
- CN202410726801.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-06
- Publication Date
- 2025-01-07
AI Technical Summary
The existing polyethylene foaming materials have shortcomings in antibacterial properties, resilience, softness and mechanical strength, which are difficult to meet the needs of sports equipment such as yoga mats, and the preparation method is complex or costly, which affects environmental friendliness.
Modified filler and chemical foaming process, through low-density polyethylene, high-density polyethylene, ethylene-vinyl acetate copolymer, modified kaolin, sodium bicarbonate, azodiamorphamide, zinc oxide, zinc stearate and The synergistic action of materials such as diisopropyl peroxide is carried out to perform hot pressing and foaming to prepare high-resistance soft foamed polyethylene material.
It significantly improves the antibacterial properties, resilience and mechanical strength of the material, enhances the hygiene, safety and service life of the material, is suitable for sports equipment and other occasions, and maintains the lightweight and low-cost characteristics of polyethylene materials.
Smart Images

Figure BDA0004878860840000141 
Figure BDA0004878860840000151
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer material foaming, and in particular to a high-resilience soft foamed polyethylene material and a preparation method thereof. Background Art
[0002] Polyethylene (PE) is widely used in packaging materials, building panels, agricultural covering films, automotive parts and other fields due to its advantages such as light weight, low cost, good chemical stability and easy processing. Traditional polyethylene foam materials have good cushioning and heat insulation properties, but have limitations in softness, resilience and mechanical strength, which restricts their use in certain specific applications.
[0003] Some lightweight and soft sports equipment such as yoga mats can easily become breeding grounds for bacteria and fungi during frequent use and sweating. Antibacterial properties can effectively inhibit the growth of microorganisms and reduce the risk of infection and allergies. Antibacterial yoga mats can reduce the frequency and difficulty of cleaning and extend the service life of the mat. Yoga mats are used in different environments, such as gyms, public places or outdoors, and may be shared by multiple people. Antibacterial properties help prevent cross-infection, and there may be more sources of microbial contamination in these places. Existing yoga mats have poor antibacterial properties, poor durability, difficulty in cleaning, and insufficient comfort and grip, which affect the effect of practice.
[0004] In order to improve the performance of polyethylene foam materials, studies have been conducted to modify polyethylene by physical or chemical methods. However, these methods often require complex processes or expensive raw materials, and while improving certain properties, they may affect other properties, such as increasing costs, reducing production efficiency, or affecting environmental friendliness. The market needs a foamed polyethylene material that not only maintains the advantages of polyethylene materials such as light weight and low cost, but also significantly improves its antibacterial properties, resilience, softness, and mechanical strength. In addition, the preparation method of the material should be simple, efficient, and environmentally friendly.
[0005] China's invention patent CN103408823B discloses a calcium carbonate-filled, high-resilience soft foamed polyethylene material, which is composed of the following raw materials by mass: 15-20 parts of PE, 5-20 parts of elastomer, 60-80 parts of modified calcium carbonate, 1-10 parts of foaming agent, and 0.5-1.5 parts of cross-linking agent. A method for preparing a calcium carbonate-filled, high-resilience soft foamed polyethylene material, characterized in that it comprises the following steps: 1) drying the calcium carbonate powder; 2) fully mixing the calcium carbonate powder obtained in the previous step with the coupling agent; 3) placing PE and the elastomer in an open mill for plasticizing; 4) adding the modified calcium carbonate, foaming agent, and cross-linking agent obtained in step 2) to the system of the previous step in sequence for mixing; 5) subjecting the mixed material to one or two hot-pressing foaming. However, the foamed polyethylene material of the invention has poor antibacterial properties and insufficient mechanical properties, and cannot meet the needs of sports equipment. Summary of the invention
[0006] In view of the deficiencies in the prior art, the present invention provides a method for preparing a high-resilience soft foamed polyethylene material. The method achieves high mechanical properties and antibacterial properties through a carefully designed modified filler and chemical foaming process, can effectively inhibit the growth of bacteria and fungi, and protect the health of users. It is particularly suitable for applications in close contact with the skin, such as sports equipment and yoga mats, to ensure hygiene and safety.
[0007] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:
[0008] A method for preparing a high-resilience soft foamed polyethylene material is as follows:
[0009] The low-density polyethylene, high-density polyethylene and elastomer are placed in an open mill for plasticizing; the modified filler, physical foaming agent, chemical foaming agent and cross-linking agent are sequentially added to the plasticized system for mixing; the mixed material is placed in a mold, the mold is placed in a flat vulcanizer, hot-pressed and foamed for 8 to 12 minutes at 160 to 180° C. and 8 to 12 MPa, the mold is opened and taken out, and lightly pressed to shape to obtain a foamed polyethylene material.
[0010] The weight proportions of the substances are: 2 to 3 parts of low-density polyethylene, 0.4 to 0.6 parts of high-density polyethylene, 1.2 to 1.8 parts of elastomer, 2 to 3 parts of modified filler, 0.2 to 0.4 parts of physical foaming agent, 0.4 to 0.6 parts of chemical foaming agent, and 0.05 to 0.2 parts of cross-linking agent.
[0011] The plasticizing temperature is 120-140° C., and the plasticizing time is 3-5 minutes.
[0012] The mixing temperature is 120-140° C., and the mixing time is 8-15 minutes.
[0013] The elastomer is one of ethylene-vinyl acetate copolymer, ethylene-propylene rubber and ethylene-propylene-diene rubber.
[0014] The cross-linking agent is dicumyl peroxide.
[0015] The chemical foaming agent is composed of azodicarbonamide, zinc oxide and zinc stearate mixed in a mass ratio of 1:0.5 to 1:2 to 4.
[0016] The physical foaming agent is sodium bicarbonate.
[0017] The preparation method of the modified filler is as follows, in parts by weight:
[0018] S1: 8 to 10 parts of kaolin and 0.4 to 0.5 parts of 3-[tri(octyloxy)silyl]propanethiol are added to 70 to 75 parts of anhydrous ethanol, heated and stirred at 50 to 60° C. for 1 to 3 hours, and then centrifuged at 13,000 to 15,000 rpm for 3 to 8 minutes, the solid is collected, washed with anhydrous ethanol, and dried in a vacuum drying oven at 40 to 60° C. for 1 to 3 hours to obtain a pretreated product;
[0019] S2: Use 8 to 10 parts of the pretreated material obtained in step S1, 0.5 to 0.6 parts of (1s-cis)-(9ci)-1-amino-2-chloro-cyclopropanecarboxylic acid and 0.1 to 0.2 parts of benzoin dimethyl ether, add them to 70 to 75 parts of anhydrous ethanol, and heat and stir the reaction at 30 to 40°C under 300 to 400W ultraviolet lamp for 2 to 3 hours. After the reaction, centrifuge at a speed of 15,000 to 17,000 rpm for 3 to 8 minutes, remove the supernatant, collect the solid, and then wash it with anhydrous ethanol, and dry it in a vacuum drying oven at 40 to 60°C for 1 to 3 hours to obtain a modified filler.
[0020] Preferably, the preparation method of the modified filler is as follows, in parts by weight:
[0021] S1: 8 to 10 parts of kaolin and 0.4 to 0.5 parts of 3-[tri(octyloxy)silyl]propanethiol are added to 70 to 75 parts of anhydrous ethanol, heated and stirred at 50 to 60° C. for 1 to 3 hours, and then centrifuged at 13,000 to 15,000 rpm for 3 to 8 minutes, the solid is collected, washed with anhydrous ethanol, and dried in a vacuum drying oven at 40 to 60° C. for 1 to 3 hours to obtain a pretreated product;
[0022] S2: 8 to 10 parts of the pretreated product obtained in step S1, 0.2 to 0.3 parts of (1s-cis)-(9ci)-1-amino-2-chloro-cyclopropanecarboxylic acid, 0.2 to 0.3 parts of 1-amino-2-vinylcyclopropanecarboxylic acid and 0.1 to 0.2 parts of benzoin dimethyl ether are added to 70 to 75 parts of anhydrous ethanol, and heated and stirred at 30 to 40°C for 2 to 3 hours under irradiation of a 300 to 400 W ultraviolet lamp. After the reaction is completed, centrifuge at a speed of 15,000 to 17,000 rpm for 3 to 8 minutes, remove the supernatant, collect the solid, wash it with anhydrous ethanol, and dry it in a vacuum drying oven at 40 to 60°C for 1 to 3 hours to obtain a modified filler.
[0023] A high-resilience soft foamed polyethylene material is made by adopting the method.
[0024] A yoga mat is prepared by adopting the high-resilience soft foamed polyethylene material.
[0025] In the preparation method of the high resilience soft foamed polyethylene material of the present invention, the functions of various substances are as follows:
[0026] Low-density polyethylene (LDPE), as one of the basic components of foaming materials, provides softness and toughness.
[0027] High-density polyethylene (HDPE) also serves as a base component, increasing the hardness and mechanical strength of the material.
[0028] Ethylene-vinyl acetate copolymer (EVA) is used as a blending material to improve the softness, elasticity and adhesion of foamed polyethylene.
[0029] Modified fillers improve the mechanical properties, heat resistance, dimensional stability of materials, and may improve the processing properties of materials.
[0030] Sodium bicarbonate, as a component of the physical foaming agent, participates in the generation of gas and promotes the foaming process.
[0031] Chemical blowing agents (azodicarbonamide, zinc oxide, zinc stearate) generate gas, form the foam structure, and provide the desired foam characteristics.
[0032] Dicumyl peroxide acts as a cross-linking agent to promote cross-linking between polyethylene molecules and enhance the strength and heat resistance of the material.
[0033] 3-[Tri(octyloxy)silyl]propanethiol is used as a silane coupling agent in pretreatment to enhance the compatibility and bonding strength between kaolin and polyethylene matrix.
[0034] (1s-cis)-(9ci)-1-amino-2-chloro-cyclopropanecarboxylic acid may be used as a reactive monomer in the preparation of modified fillers to enhance the surface modification of fillers.
[0035] Benzoin dimethyl ether is used as a photoinitiator for UV curing reaction to promote the modification reaction.
[0036] Anhydrous ethanol is used as a solvent to dissolve and disperse the reactants during the preparation of the modified filler.
[0037] Through the synergistic effect of these substances, the preparation method of the present invention can produce a soft foamed polyethylene material with high resilience, softness and good mechanical properties.
[0038] Compared with the prior art, it has the following beneficial effects:
[0039] 1) The high-resilience soft foamed polyethylene material of the present invention improves the mechanical strength and toughness of the foamed polyethylene and enhances the antibacterial property by using modified fillers.
[0040] 2) The high resilience soft foamed polyethylene material of the present invention adopts a specific combination of chemical foaming agents to produce a uniform bubble structure during the foaming process, which helps to improve the resilience and softness of the material.
[0041] 3) The addition of sodium bicarbonate and diisopropylbenzene peroxide during the mixing process of the high resilience soft foamed polyethylene material of the present invention helps to improve the fluidity and stability of the polymer melt, thereby improving the processing performance.
[0042] 4) The high-resilience soft foamed polyethylene material of the present invention can be prepared into a foamed polyethylene material with high resilience by precisely controlling the conditions of hot-pressing foaming.
[0043] 5) The foamed polyethylene material of the present invention can be widely used in fields requiring good cushioning, elasticity and softness, such as automobile interiors, furniture, shoe materials, sports equipment, including yoga mats, etc. DETAILED DESCRIPTION
[0044] Main sources of substances:
[0045] Low-density polyethylene: Honghua Plastic Technology (Dongguan) Co., Ltd., product number: DFDA-7042 (pink).
[0046] High-density polyethylene: Suzhou Lingsu Plastic Technology Co., Ltd., item number: LH606.
[0047] Ethylene-vinyl acetate copolymer: Suzhou Kunpeng Plastic Chemical Co., Ltd., item number: 880.
[0048] Kaolin: Lingshou County Tuyun Mineral Products Processing Plant, product number: GL-236, specification: 1250 mesh.
[0049] 3-[Tri(octyloxy)silyl]propanethiol: CAS number: 94291-66-4.
[0050] (1s-cis)-(9ci)-1-amino-2-chloro-cyclopropanecarboxylic acid: CAS number: 163180-55-0.
[0051] 3-[Tris(2-ethoxyethoxy)silyl]propanethiol: CAS number: 67724-41-8.
[0052] 2-Methyl-3-(triethoxysilyl)propanethiol: CAS number: 17980-28-8.
[0053] Mercaptopropyltrimethoxysilane: CAS number: 4420-74-0.
[0054] (3-Mercaptopropyl)triethoxysilane: CAS number: 14814-09-6.
[0055] Y-Chlorodemethylvaline: CAS number: 76265-38-8.
[0056] (1R,2S)-1-tert-Butyloxycarbonylamino-2-vinylcyclopropanecarboxylic acid: CAS number: 159622-10-3.
[0057] 1-Amino-2-vinylcyclopropanecarboxylic acid: CAS number: 80003-54-9.
[0058] Wollastonite: Lingshou County Dexu Mining Co., Ltd., product number: dx-ghs, specification: 1250 mesh.
[0059] Calcium carbonate: Changxing Qingsheng Calcium Industry Co., Ltd., item number: 002, particle size: 1500 mesh.
[0060] The design idea of the present invention is to modify the filler by specific chemical and physical methods, and combine it with a specific polymer matrix and other additives to prepare a foamed polyethylene material with high resilience and soft properties. The specific design ideas are as follows:
[0061] Low-density polyethylene (LDPE), high-density polyethylene (HDPE), and ethylene-vinyl acetate copolymer (EVA) are used as matrices to obtain the required softness and mechanical properties.
[0062] Kaolin was selected as the base material of the filler and pretreated with 3-[tri(octyloxy)silyl]propanethiol to enhance its compatibility and dispersibility with the polymer matrix. (1s-cis)-(9ci)-1-amino-2-chloro-cyclopropanecarboxylic acid and benzoin dimethyl ether were used for surface modification to introduce functional groups and further improve the compatibility with the polymer.
[0063] During the modification process, a 350W ultraviolet lamp was used to promote the reaction between the modifier and the kaolin surface and enhance the modification effect.
[0064] Azodicarbonamide, zinc oxide and zinc stearate are selected as chemical foaming agents, and gas is generated through their thermal decomposition to form a foam structure.
[0065] Dicumyl peroxide is used as a cross-linking agent to strengthen the connection between polymer chains and improve the mechanical strength and stability of the material.
[0066] By controlling the conditions of hot-press foaming (temperature, pressure and time), the foam structure can be precisely adjusted to achieve the desired foaming effect.
[0067] The foamed material is lightly pressed to shape to ensure that the material obtains a uniform pore structure and the required physical properties.
[0068] Throughout the preparation process, the temperature, time and conditions of steps such as plasticating, mixing, foaming and drying are carefully designed to ensure the performance of the final product.
[0069] Through this design concept, the present invention aims to prepare foamed polyethylene materials with excellent resilience, softness and mechanical strength, which can be used in applications requiring good cushioning and elastic properties.
[0070] Example 1
[0071] A method for preparing a high-resilience soft foamed polyethylene material is as follows:
[0072] 2.5 kg of low-density polyethylene, 0.5 kg of high-density polyethylene and 1.5 kg of ethylene-vinyl acetate copolymer are placed in an open mill for plasticizing at a temperature of 135°C for 4 minutes; 2.5 kg of modified filler, 0.3 kg of sodium bicarbonate, 0.5 kg of chemical foaming agent and 0.1 kg of diisopropylbenzene peroxide are added to the above-mentioned plasticized system in sequence for mixing at a temperature of 130°C for 10 minutes; the mixed material is placed in a mold, the mold is placed in a flat vulcanizer, hot-pressed and foamed at 170°C and 10 MPa for 10 minutes, the mold is opened and taken out, and lightly pressed to shape to obtain a foamed polyethylene material.
[0073] The chemical foaming agent is composed of azodicarbonamide, zinc oxide and zinc stearate mixed in a mass ratio of 1:0.8:3.
[0074] The preparation method of the modified filler is as follows:
[0075] S1: 9 kg of kaolin and 0.45 kg of 3-[tri(octyloxy)silyl]propanethiol were added to 72 kg of anhydrous ethanol, heated and stirred at 55° C. for 2 hours, and then centrifuged at 14,000 rpm for 5 minutes, the solid was collected, washed with anhydrous ethanol, and dried in a vacuum drying oven at 50° C. for 2 hours to obtain a pretreated product;
[0076] S2: 9 kg of the pretreated material obtained in step S1, 0.54 kg of (1s-cis)-(9ci)-1-amino-2-chloro-cyclopropanecarboxylic acid and 0.18 kg of benzoin dimethyl ether were added to 72 kg of anhydrous ethanol, and heated and stirred at 35°C for 2.5 hours under 350 W ultraviolet light. After the reaction, the mixture was centrifuged at a speed of 16,000 rpm for 6 minutes, the supernatant was removed, the solid was collected, and then washed with anhydrous ethanol and dried in a vacuum drying oven at 50°C for 2 hours to obtain a modified filler.
[0077] Example 2
[0078] The preparation method of a high-resilience soft foamed polyethylene material is basically the same as that of Example 1, the only difference being that the preparation method of the modified filler is different.
[0079] The preparation method of the modified filler is as follows:
[0080] S1: 9 kg of kaolin and 0.45 kg of 3-[tri(2-ethoxyethoxy)silyl]propanethiol were added to 72 kg of anhydrous ethanol, heated and stirred at 55° C. for 2 hours, and then centrifuged at 14,000 rpm for 5 minutes, the solid was collected, washed with anhydrous ethanol, and dried in a vacuum drying oven at 50° C. for 2 hours to obtain a pretreated product;
[0081] S2: 9 kg of the pretreated material obtained in step S1, 0.54 kg of (1s-cis)-(9ci)-1-amino-2-chloro-cyclopropanecarboxylic acid and 0.18 kg of benzoin dimethyl ether were added to 72 kg of anhydrous ethanol, and heated and stirred at 35°C for 2.5 hours under 350 W ultraviolet light. After the reaction, the mixture was centrifuged at a speed of 16,000 rpm for 6 minutes, the supernatant was removed, the solid was collected, and then washed with anhydrous ethanol and dried in a vacuum drying oven at 50°C for 2 hours to obtain a modified filler.
[0082] Example 3
[0083] The preparation method of a high-resilience soft foamed polyethylene material is basically the same as that of Example 1, the only difference being that the preparation method of the modified filler is different.
[0084] The preparation method of the modified filler is as follows:
[0085] S1: 9 kg of kaolin and 0.45 kg of 2-methyl-3-(triethoxysilyl)propanethiol were added to 72 kg of anhydrous ethanol, heated and stirred at 55° C. for 2 hours, and then centrifuged at 14,000 rpm for 5 minutes, the solid was collected, washed with anhydrous ethanol, and dried in a vacuum drying oven at 50° C. for 2 hours to obtain a pretreated product;
[0086] S2: 9 kg of the pretreated material obtained in step S1, 0.54 kg of (1s-cis)-(9ci)-1-amino-2-chloro-cyclopropanecarboxylic acid and 0.18 kg of benzoin dimethyl ether were added to 72 kg of anhydrous ethanol, and heated and stirred at 35°C for 2.5 hours under 350 W ultraviolet light. After the reaction, the mixture was centrifuged at a speed of 16,000 rpm for 6 minutes, the supernatant was removed, the solid was collected, and then washed with anhydrous ethanol and dried in a vacuum drying oven at 50°C for 2 hours to obtain a modified filler.
[0087] Example 4
[0088] The preparation method of a high-resilience soft foamed polyethylene material is basically the same as that of Example 1, the only difference being that the preparation method of the modified filler is different.
[0089] The preparation method of the modified filler is as follows:
[0090] S1: 9 kg of kaolin and 0.45 kg of mercaptopropyltrimethoxysilane were added to 72 kg of anhydrous ethanol, heated and stirred at 55° C. for 2 hours, and then centrifuged at 14,000 rpm for 5 minutes, the solid was collected, washed with anhydrous ethanol, and dried in a vacuum drying oven at 50° C. for 2 hours to obtain a pretreated product;
[0091] S2: 9 kg of the pretreated material obtained in step S1, 0.54 kg of (1s-cis)-(9ci)-1-amino-2-chloro-cyclopropanecarboxylic acid and 0.18 kg of benzoin dimethyl ether were added to 72 kg of anhydrous ethanol, and heated and stirred at 35°C for 2.5 hours under 350 W ultraviolet light. After the reaction, the mixture was centrifuged at a speed of 16,000 rpm for 6 minutes, the supernatant was removed, the solid was collected, and then washed with anhydrous ethanol and dried in a vacuum drying oven at 50°C for 2 hours to obtain a modified filler.
[0092] Example 5
[0093] The preparation method of a high-resilience soft foamed polyethylene material is basically the same as that of Example 1, the only difference being that the preparation method of the modified filler is different.
[0094] The preparation method of the modified filler is as follows:
[0095] S1: 9 kg of kaolin and 0.45 kg of (3-mercaptopropyl) triethoxysilane were added to 72 kg of anhydrous ethanol, heated and stirred at 55° C. for 2 hours, and then centrifuged at 14,000 rpm for 5 minutes, the solid was collected, washed with anhydrous ethanol, and dried in a vacuum drying oven at 50° C. for 2 hours to obtain a pretreated product;
[0096] S2: 9 kg of the pretreated material obtained in step S1, 0.54 kg of (1s-cis)-(9ci)-1-amino-2-chloro-cyclopropanecarboxylic acid and 0.18 kg of benzoin dimethyl ether were added to 72 kg of anhydrous ethanol, and heated and stirred at 35°C for 2.5 hours under 350 W ultraviolet light. After the reaction, the mixture was centrifuged at a speed of 16,000 rpm for 6 minutes, the supernatant was removed, the solid was collected, and then washed with anhydrous ethanol and dried in a vacuum drying oven at 50°C for 2 hours to obtain a modified filler.
[0097] Example 6
[0098] The preparation method of a high-resilience soft foamed polyethylene material is basically the same as that of Example 1, the only difference being that the preparation method of the modified filler is different.
[0099] The preparation method of the modified filler is as follows:
[0100] S1: 9 kg of kaolin and 0.45 kg of 3-[tri(octyloxy)silyl]propanethiol were added to 72 kg of anhydrous ethanol, heated and stirred at 55° C. for 2 hours, and then centrifuged at 14,000 rpm for 5 minutes, the solid was collected, washed with anhydrous ethanol, and dried in a vacuum drying oven at 50° C. for 2 hours to obtain a pretreated product;
[0101] S2: 9 kg of the pretreated material obtained in step S1, 0.54 kg of Y-chlorodemethylvaline and 0.18 kg of dimethyl benzoate were added to 72 kg of anhydrous ethanol, and heated and stirred at 35°C for 2.5 hours under irradiation with a 350 W ultraviolet lamp. After the reaction, the mixture was centrifuged at a speed of 16,000 rpm for 6 minutes, the supernatant was removed, the solid was collected, and then washed with anhydrous ethanol and dried in a vacuum drying oven at 50°C for 2 hours to obtain a modified filler.
[0102] Example 7
[0103] The preparation method of a high-resilience soft foamed polyethylene material is basically the same as that of Example 1, the only difference being that the preparation method of the modified filler is different.
[0104] The preparation method of the modified filler is as follows:
[0105] S1: 9 kg of kaolin and 0.45 kg of 3-[tri(octyloxy)silyl]propanethiol were added to 72 kg of anhydrous ethanol, heated and stirred at 55° C. for 2 hours, and then centrifuged at 14,000 rpm for 5 minutes, the solid was collected, washed with anhydrous ethanol, and dried in a vacuum drying oven at 50° C. for 2 hours to obtain a pretreated product;
[0106] S2: Use 9 kg of the pretreated material obtained in step S1, 0.54 kg of (1R, 2S)-1-tert-butoxycarbonylamino-2-vinylcyclopropanecarboxylic acid and 0.18 kg of benzoin dimethyl ether, add them to 72 kg of anhydrous ethanol, and heat and stir the reaction at 35°C under 350 W ultraviolet lamp for 2.5 hours. After the reaction, centrifuge at a speed of 16,000 rpm for 6 minutes, remove the supernatant, collect the solid, and then wash it with anhydrous ethanol. Dry it in a vacuum drying oven at 50°C for 2 hours to obtain a modified filler.
[0107] Example 8
[0108] The preparation method of a high-resilience soft foamed polyethylene material is basically the same as that of Example 1, the only difference being that the preparation method of the modified filler is different.
[0109] The preparation method of the modified filler is as follows:
[0110] S1: 9 kg of kaolin and 0.45 kg of 3-[tri(octyloxy)silyl]propanethiol were added to 72 kg of anhydrous ethanol, heated and stirred at 55° C. for 2 hours, and then centrifuged at 14,000 rpm for 5 minutes, the solid was collected, washed with anhydrous ethanol, and dried in a vacuum drying oven at 50° C. for 2 hours to obtain a pretreated product;
[0111] S2: 9 kg of the pretreated material obtained in step S1, 0.54 kg of 1-amino-2-vinylcyclopropanecarboxylic acid and 0.18 kg of benzoin dimethyl ether were added to 72 kg of anhydrous ethanol, and heated and stirred for reaction at 35°C for 2.5 hours under irradiation of a 350 W ultraviolet lamp. After the reaction, the mixture was centrifuged at a speed of 16,000 rpm for 6 minutes, the supernatant was removed, the solid was collected, and then washed with anhydrous ethanol and dried in a vacuum drying oven at 50°C for 2 hours to obtain a modified filler.
[0112] Example 9
[0113] The preparation method of a high-resilience soft foamed polyethylene material is basically the same as that of Example 1, the only difference being that the preparation method of the modified filler is different.
[0114] The preparation method of the modified filler is as follows:
[0115] S1: 9 kg of kaolin and 0.45 kg of 3-[tri(octyloxy)silyl]propanethiol were added to 72 kg of anhydrous ethanol, heated and stirred at 55° C. for 2 hours, and then centrifuged at 14,000 rpm for 5 minutes, the solid was collected, washed with anhydrous ethanol, and dried in a vacuum drying oven at 50° C. for 2 hours to obtain a pretreated product;
[0116] S2: 9 kg of the pretreated material obtained in step S1, 0.27 kg of (1s-cis)-(9ci)-1-amino-2-chloro-cyclopropanecarboxylic acid, 0.27 kg of 1-amino-2-vinylcyclopropanecarboxylic acid and 0.18 kg of benzoin dimethyl ether were added to 72 kg of anhydrous ethanol, and heated and stirred at 35°C for 2.5 hours under 350 W ultraviolet light. After the reaction, the mixture was centrifuged at a speed of 16,000 rpm for 6 minutes, the supernatant was removed, the solid was collected, and then washed with anhydrous ethanol and dried in a vacuum drying oven at 50°C for 2 hours to obtain a modified filler.
[0117] Comparative Example 1
[0118] The preparation method of a high-resilience soft foamed polyethylene material is basically the same as that of Example 1, the only difference being that the preparation method of the modified filler is different.
[0119] The preparation method of the modified filler is as follows:
[0120] S1: 9 kg of wollastonite and 0.45 kg of 3-[tri(octyloxy)silyl]propanethiol were added to 72 kg of anhydrous ethanol, heated and stirred at 55° C. for 2 hours, and then centrifuged at 14,000 rpm for 5 minutes, the solid was collected, washed with anhydrous ethanol, and dried in a vacuum drying oven at 50° C. for 2 hours to obtain a pretreated product;
[0121] S2: 9 kg of the pretreated material obtained in step S1, 0.54 kg of (1s-cis)-(9ci)-1-amino-2-chloro-cyclopropanecarboxylic acid and 0.18 kg of benzoin dimethyl ether were added to 72 kg of anhydrous ethanol, and heated and stirred at 35°C for 2.5 hours under 350 W ultraviolet light. After the reaction, the mixture was centrifuged at a speed of 16,000 rpm for 6 minutes, the supernatant was removed, the solid was collected, and then washed with anhydrous ethanol and dried in a vacuum drying oven at 50°C for 2 hours to obtain a modified filler.
[0122] Comparative Example 2
[0123] The preparation method of a high-resilience soft foamed polyethylene material is basically the same as that of Example 1, the only difference being that the preparation method of the modified filler is different.
[0124] The preparation method of the modified filler is as follows:
[0125] S1: 9 kg of calcium carbonate and 0.45 kg of 3-[tri(octyloxy)silyl]propanethiol were added to 72 kg of anhydrous ethanol, heated and stirred at 55° C. for 2 hours, and then centrifuged at 14,000 rpm for 5 minutes, the solid was collected, washed with anhydrous ethanol, and dried in a vacuum drying oven at 50° C. for 2 hours to obtain a pretreated product;
[0126] S2: 9 kg of the pretreated material obtained in step S1, 0.54 kg of (1s-cis)-(9ci)-1-amino-2-chloro-cyclopropanecarboxylic acid and 0.18 kg of benzoin dimethyl ether were added to 72 kg of anhydrous ethanol, and heated and stirred at 35°C for 2.5 hours under 350 W ultraviolet light. After the reaction, the mixture was centrifuged at a speed of 16,000 rpm for 6 minutes, the supernatant was removed, the solid was collected, and then washed with anhydrous ethanol and dried in a vacuum drying oven at 50°C for 2 hours to obtain a modified filler.
[0127] Comparative Example 3
[0128] A method for preparing a high-resilience soft foamed polyethylene material is as follows:
[0129] 2.5kg of low-density polyethylene, 0.5kg of high-density polyethylene and 1.5kg of ethylene-vinyl acetate copolymer are placed in an open mill for plasticizing at a temperature of 135°C for 4 minutes; 5.5kg of kaolin, 0.3kg of sodium bicarbonate, 0.5kg of chemical foaming agent and 0.1kg of diisopropylbenzene peroxide are added to the above-mentioned plasticized system in sequence for mixing at a temperature of 130°C for 10 minutes; the mixed material is placed in a mold, the mold is placed in a flat vulcanizer, hot-pressed and foamed at 170°C and 10MPa for 10 minutes, the mold is opened and taken out, and lightly pressed to shape to obtain a foamed polyethylene material.
[0130] The chemical foaming agent is composed of azodicarbonamide, zinc oxide and zinc stearate mixed in a mass ratio of 1:0.8:3.
[0131] Comparative Example 4
[0132] A method for preparing a high-resilience soft foamed polyethylene material is as follows:
[0133] 2.5kg of low-density polyethylene, 0.5kg of high-density polyethylene and 1.5kg of ethylene-vinyl acetate copolymer are placed in an open mill for plasticizing at a temperature of 135°C for 4 minutes; 0.3kg of sodium bicarbonate, 0.5kg of a chemical foaming agent and 0.1kg of diisopropylbenzene peroxide are added to the plasticized system in sequence for mixing at a temperature of 130°C for 10 minutes; the mixed material is placed in a mold, the mold is placed in a flat vulcanizer, hot-pressed and foamed at 170°C and 10MPa for 10 minutes, the mold is opened and taken out, and lightly pressed to shape to obtain a foamed polyethylene material.
[0134] The chemical foaming agent is composed of azodicarbonamide, zinc oxide and zinc stearate mixed in a mass ratio of 1:0.8:3.
[0135] Test Example 1
[0136] Antimicrobial testing
[0137] Sample preparation: The foamed polyethylene materials of Examples 1, 6 to 9 and Comparative Examples 1 to 4 were sterilized with 75% ethanol aqueous solution and naturally air-dried.
[0138] A bacterial solution of a standard strain of Escherichia coli (ATCC 25922) was prepared and adjusted to a predetermined concentration using sterile water.
[0139] Inoculation and culture: Evenly drip 0.2 ml of the adjusted concentration of E. coli liquid on the surface of the sample to be tested. Cover the liquid with a 0.1 mm thick, 4.0 cm × 4.0 cm polyethylene transparent film to ensure that the liquid is evenly distributed between the film and the sample to form a thin layer. Place the sample covered with the film in a constant temperature environment of 37°C and maintain a relative humidity of 90% for 24 hours.
[0140] Colony count: After the incubation, use sterile water to gently rinse the sample surface to elute the attached bacteria. Dilute the eluted bacterial solution in series to form different concentration gradients. Take 0.1 ml of the diluted bacterial solution and evenly spread it on the pre-prepared and sterilized agar plate. Place the agar plate coated with bacteria in a constant temperature incubator at 37°C and continue to incubate for 24 hours. After the incubation is completed, observe the growth of colonies on the agar plate, record the results, and obtain the antibacterial rate. Use a sterile blank plate to set up a negative control group and perform the same operation to verify the sterility of the experimental conditions.
[0141] The test results are shown in Table 1.
[0142] Table 1
[0143]
[0144]
[0145] Test Example 2
[0146] Mechanical properties test
[0147] The tensile strength and elongation at break of the foamed polyethylene materials prepared in the examples of the present invention and the comparative examples were measured according to the method specified in GB / T 6344-2008 “Determination of tensile strength and elongation at break of flexible foamed polymeric materials”. The test results are shown in Table 2.
[0148] Table 2
[0149] Experimental protocol Tensile strength(MPa) Elongation at break (%) Example 1 3.89 287.8 Example 2 3.74 271.5 Example 3 3.69 268.6 Example 4 3.67 266.9 Example 5 3.64 264.7 Example 6 3.54 258.9 Example 7 3.58 261.5 Example 8 3.76 272.5 Example 9 3.97 291.7 Comparative Example 1 3.48 252.6 Comparative Example 2 3.42 245.6 Comparative Example 3 3.14 224.0 Comparative Example 4 2.89 205.9
[0150] It can be seen from test examples 1 to 2 that the foamed polyethylene material obtained in Example 9 of the present invention has good antibacterial rate and mechanical properties.
[0151] In Examples 1 to 5, from the perspective of molecular structure, 3-[tri(octyloxy)silyl]propanethiol shows better mechanical properties than other silane compounds in Example 1, which may be due to the longer octyloxy chain in 3-[tri(octyloxy)silyl]propanethiol, which may enhance the compatibility with the polyethylene matrix, because the long chain can be better inserted between polyethylene chains, reducing interfacial tension, thereby improving the mechanical properties of the overall material. Longer alkoxy chains may also form a thicker modified layer on the surface of the filler, which helps to improve the dispersibility of the filler in the polyethylene matrix, reduce agglomeration, and thus improve the uniformity and mechanical properties of the material. The thiol group has a high reactivity and can form a strong coordination bond with the metal ions on the surface of kaolin, enhancing the dispersibility of the filler and the adhesion to the matrix. Under ultraviolet light irradiation, 3-[tri(octyloxy)silyl]propanethiol may be more likely to combine with other reactants (such as (1s-cis)-(9ci)-1-amino-2-chloro-cyclopropanecarboxylic acid) to form a more complex three-dimensional network structure, which helps to improve the mechanical properties of the material.
[0152] Compared with Examples 1, 6 to 9, from the perspective of molecular structure, the effects of different compounds on the performance of high-resilience soft foamed polyethylene materials are mainly related to their chemical structure, the type and number of functional groups, and their interaction with the polymer matrix. (1s-cis)-(9ci)-1-amino-2-chloro-cyclopropanecarboxylic acid contains amino and carboxylic acid functional groups, which can form hydrogen bonds or ionic bonds with the hydroxyl groups on the surface of kaolin, thereby enhancing the interfacial bonding between the filler and the polymer matrix. At the same time, the presence of chlorine atoms may increase the antibacterial properties of the molecule. Y-chlorodemethylvaline contains carboxyl groups, which can form strong chemical bonds with kaolin, and the chlorinated groups may provide additional van der Waals forces or dipole-dipole interactions, which help to improve the antibacterial and mechanical properties of the material. (1R, 2S)-1-tert-butyloxycarbonylamino-2-vinylcyclopropanecarboxylic acid, a chiral molecule, contains tert-butyloxycarbonyl, which may increase the steric hindrance of the molecule, affecting the bonding mode with kaolin and the compatibility with the polymer matrix. 1-Amino-2-vinylcyclopropanecarboxylic acid contains amino and carboxylic acid functional groups, similar to (1s-cis)-(9ci)-1-amino-2-chloro-cyclopropanecarboxylic acid, which helps to enhance the bonding between the filler and the polymer matrix. The compounding of (1s-cis)-(9ci)-1-amino-2-chloro-cyclopropanecarboxylic acid and 1-amino-2-vinylcyclopropanecarboxylic acid may have a synergistic effect. The two different functional groups form a variety of interactions with kaolin and the polymer matrix, improving the comprehensive performance of the material. Different functional groups (amino, carboxylic acid, chlorinated) form multiple chemical bonds with kaolin and polyethylene matrix, enhancing the interfacial bonding. The reaction of functional groups with kaolin helps to improve the dispersibility of fillers in the polymer matrix, reduce agglomeration, and improve the compatibility of inorganic fillers with organic matrices. The chlorinated functional groups may give the material certain antibacterial properties. Due to the enhanced bonding between the filler and the matrix, the tensile strength and elongation at break of the foamed polyethylene may be improved.
[0153] Example 1 Compared with the comparative example, the performance differences of the three fillers, kaolin, wollastonite and calcium carbonate, in the foamed polyethylene material may be related to their chemical composition, crystal structure, surface characteristics and interaction with the polymer matrix. Kaolin is a layered silicate mineral with a high specific surface area and a layered structure, which can provide high mechanical strength and good dispersibility. Wollastonite is a calcium silicate mineral that generally has good chemical corrosion resistance and thermal stability. Calcium carbonate is a common inorganic salt widely used as a filler, with high hardness and good wear resistance.
[0154] The surface of kaolin usually carries a negative charge, which helps to enhance the interaction with the polyethylene matrix and improve the overall performance of the material. The layered structure of kaolin may help to form a better dispersion in the polymer matrix and avoid agglomeration, thereby improving the uniformity and mechanical properties of the material. The layered structure of kaolin may help to adsorb antibacterial agents or antibacterial ions, thereby improving the antibacterial properties of the material. The surface properties of wollastonite and calcium carbonate may be different from those of kaolin, which may affect their compatibility and dispersibility with the polymer matrix. Moreover, they do not have this adsorption property, or their surface is not conducive to the fixation of antibacterial substances, resulting in poor antibacterial properties. The use of kaolin in Example 1 may be due to its unique chemical composition, crystal structure and surface characteristics, which form a strong interaction with the polyethylene matrix, thereby improving the antibacterial rate and mechanical properties of the foamed polyethylene material.
Claims
1. A method for preparing a high-resilience soft foamed polyethylene material, characterized in that: Here’s how: The low-density polyethylene, high-density polyethylene and elastomer are placed in an open mill for plasticizing; the modified filler, physical foaming agent, chemical foaming agent and cross-linking agent are sequentially added to the plasticized system for mixing; the mixed material is placed in a mold, the mold is placed in a flat vulcanizer, hot-pressed and foamed for 8 to 12 minutes at 160 to 180° C. and 8 to 12 MPa, the mold is opened and taken out, and lightly pressed to shape to obtain a foamed polyethylene material.
2. The method for preparing the high resilience soft foamed polyethylene material according to claim 1, characterized in that: The weight proportions of the substances are: 2 to 3 parts of low-density polyethylene, 0.4 to 0.6 parts of high-density polyethylene, 1.2 to 1.8 parts of elastomer, 2 to 3 parts of modified filler, 0.2 to 0.4 parts of physical foaming agent, 0.4 to 0.6 parts of chemical foaming agent, and 0.05 to 0.2 parts of cross-linking agent.
3. The method for preparing the high resilience soft foamed polyethylene material according to claim 1, characterized in that: The plasticizing temperature is 120-140°C, and the plasticizing time is 3-5 minutes; The mixing temperature is 120-140° C., and the mixing time is 8-15 minutes.
4. The method for preparing the high resilience soft foamed polyethylene material according to claim 1 or 2, characterized in that: The elastomer is one of ethylene-vinyl acetate copolymer, ethylene-propylene rubber and ethylene-propylene-diene rubber.
5. The method for preparing the high resilience soft foamed polyethylene material according to claim 1 or 2, characterized in that: The cross-linking agent is dicumyl peroxide.
6. The method for preparing the high resilience soft foamed polyethylene material according to claim 1 or 2, characterized in that: The chemical foaming agent is composed of azodicarbonamide, zinc oxide and zinc stearate mixed in a mass ratio of 1:0.5 to 1:2 to 4.
7. The method for preparing the high resilience soft foamed polyethylene material according to claim 1 or 2, characterized in that: The physical foaming agent is sodium bicarbonate.
8. The method for preparing the high resilience soft foamed polyethylene material according to claim 1 or 2, characterized in that: The preparation method of the modified filler is as follows, in parts by weight: S1: 8 to 10 parts of kaolin and 0.4 to 0.5 parts of 3-[tri(octyloxy)silyl]propanethiol are added to 70 to 75 parts of anhydrous ethanol, heated and stirred at 50 to 60° C. for 1 to 3 hours, and then centrifuged at 13,000 to 15,000 rpm for 3 to 8 minutes, the solid is collected, washed with anhydrous ethanol, and dried in a vacuum drying oven at 40 to 60° C. for 1 to 3 hours to obtain a pretreated product; S2: Use 8 to 10 parts of the pretreated material obtained in step S1, 0.5 to 0.6 parts of (1s-cis)-(9ci)-1-amino-2-chloro-cyclopropanecarboxylic acid and 0.1 to 0.2 parts of benzoin dimethyl ether, add them to 70 to 75 parts of anhydrous ethanol, and heat and stir the reaction at 30 to 40°C under 300 to 400W ultraviolet lamp for 2 to 3 hours. After the reaction, centrifuge at a speed of 15,000 to 17,000 rpm for 3 to 8 minutes, remove the supernatant, collect the solid, and then wash it with anhydrous ethanol, and dry it in a vacuum drying oven at 40 to 60°C for 1 to 3 hours to obtain a modified filler.
9. A high resilience soft foamed polyethylene material, characterized in that: The method is prepared according to any one of claims 1 to 8.
10. A yoga mat, characterized in that: It is made of the high-resilience soft foamed polyethylene material as described in claim 9.
Citation Information
Patent Citations
High-filled, high-resilience, soft foamed polyethylene material with calcium carbonate and its preparation method
CN103408823B
High-fill high-resilience soft expanded polyethylene material and preparation method thereof
CN103694542A
Halogen-Free Flame-Retardant Polyolefin Composite Foam Material And Preparation Method Thereof
US20160304691A1